Modeling the structural relationship between early maternal maladaptive schemas and children\'s temperamental problems: The mediating role of child adjustment - Mohammad Kazem Salamat; Masoud Hejazi; Siros Izadpanah; Zekrollah Morovati (Zanjan University of Medical Sciences and Health Services, 2019)
Background: The characteristics of maternal schemas play an important role in children's psychological health. Identifying the mechanism of the relationship between maternal schema and temperament problems can be the focus of therapeutic interventions. Objectives: The aim of the present study was to investigate the ways to predict the relationship between early maladaptive schemas of mothers and childrenchr('39')s temperament problems with child adjustment as the mediator. Methods: This is a descriptive-analytic study based on correlation and path analyses. The sample consisted of 447 Zanjan preschool students who were selected through multistage cluster sampling method. The data were collected using a questionnaire, and the parents of preschool children answered early maladaptive schemas Yang, adolescent child adjustment, and the Malahotra temperamental questionnaires. Pearsonchr('39')s correlation coefficient and path analysis were used to analyze the data. Results: The results related to the preschool children and their mothers showed that the direct estimation coefficients of temperament problems based on components of maladaptive schemas were between-09 % to -20%. Besides, the direct coefficients of temperamental problems based on child adjustment were 46%. Overall, maternal maladaptive schemas accounted for 08% of the variance of adjustment and .33% of the variance in temperamental problems (P = 0.01). Conclusion: According to the results, it seems that measuring and detecting maladaptive schema of mothers and identifying the type of maladaptive schema and curing them can lead to children adjustment and alleviate their temperamental problems.